Simultaneous detection of G6PD mutations using SNPscan in a multiethnic minority area of Southwestern China - Wei, Huagui; Wang, Chunfang; Huang, Weiyi; He, Liqiao; Liu, Yaqun; Huang, Huiying; Chen, Wencheng; Zheng, Yuzhong; Xu, Guidan; Lin, Liyun; Wei, Wujun; Chen, Weizhong; et al. (Frontiers in Genetics, 2023)
Objectives: Baise, a multiethnic inhabited area of southwestern China, is a historical malaria-endemic area with a high prevalence of G6PD deficiency. However, few studies of G6PD deficiency have been conducted in this region. Therefore, we performed a genetic analysis of G6PD deficiency in the Baise population from January 2020 to June 2021. Methods: A SNPscan assay was developed to simultaneously detect 33 common Chinese G6PD mutations. 30 G6PD-deficient samples were used for the method’s validation. Then, a total of 709 suspected G6PD-deficient samples collated from the Baise population were evaluated for G6PD status, type of mutation and effect of mutations. Results: The SNPscan test had a sensitivity of 100% [95% confidence interval (CI): 94.87%–100%] and a specificity of 100% (95% CI: 87.66%–100%) for identifying G6PD mutations. A total of fifteen mutations were identified from 76.72% (544/709) of the samples. The most common mutation was discovered to be G6PD Kaiping (24.12%), followed by G6PD Canton (17.91%), and G6PD Gaohe (11.28%). We compared the G6PD mutation spectrum among Zhuang, Han and other Southeast Asian populations, and the Zhuang population’s mutation distribution was quite similar to that in the Han population. Conclusion: This study provided a detailed G6PD mutation spectrum in Baise of southwestern China and will be valuable for the diagnosis and research of G6PD deficiency in this area. Furthermore, the SNPscan assay could be used to quickly diagnose these G6PD mutations accurately.